Costos financieros (ingresos y egresos) en el periodo fiscal 2021 de la exportadora de cacao Ruvicoa Cía. Ltda. Del cantón Babahoyo, provincia de Los Ríos. - Buenaire De La Cruz, William Agustín (2022)
Accounting studies within a fiscal period are advantageous to be able to know the economic growth or decline of a company in the months of productivity worked, a fiscal period can be quarterly, semi-annually or annually, it all depends on how the company wants to work it. In this case the company RUVICOA CIA. LTDA. It works annually, from January to December. In the present investigation it is possible to determine the control of the income and expenses of the company LTDA. In the fiscal period of the year 2021, with a mixed study methodology, that is, obtaining accounting results for the year 2021 by the company and interpretation of an interview with the administrator of the institution. On the other hand, literary information is obtained from internet sources to support the investigation. Once the information has been obtained by the company, an interpretation of the documentation is made with a mixed approach so that the work has a total of six determining points in the conclusion, which indicate that the company has a profit of net profit in $189,598.07. Therefore, in the interview with the administrator, he determines that the 2021 period was a stable year in terms of the purchase and export of cocoa despite an exit from the COVID-19 pandemic.